Construção de uma incubadora de ovos automatizada com Arduino com controle de temperatura utilizando PID, Fuzzy e GPC - Cavenago, Gustavo Flore (2016)
The poultry industry farming has a fundamental role in the lives of people, being responsible for intensively producing chicken meat, marketed in the markets. Such production is due to egg incubators, which automates and provides a favorable environment for egg development. Thus, the main focus of this work was to analyze the PID, Fuzzy and GPC methods in the temperature control of an egg incubator, ensuring that the temperature is maintained at the desired reference (main quality assurance). A prototype was built with support for 12 eggs and automated with the Arduino platform. During the study the need to interact and modify some methods was verified in the attempt to obtain better internal temperature responses, using genetic algorithms to optimize the parameters of the controllers. After the study, the chosen controller was implemented and the prototype operation was verified, using a simple controller (double proportional) of easy implementation, meeting the requirements of the initial proposal of the work with effectiveness.